Rekonstruksi Pengajaran dan Kajian Fiqih Pada Era Cyber - Hasani, Ahmad; Hamid, Abdulloh (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
Science and technology are growing rapidly. The materialist and consumptive lifestyle of many influences the current generation mindset. The Westernization also contributes to the mindset which in the end occurs the dichotomy of science and unfortunately many are ignoring to study the Fiqh more in line with pragmatism of thought patterns. The process of learning and study of fiqh becomes important to be intualized in the current life so that from the formulation of appropriate methods of teaching and study will produce the right output as expected the human being able to carry out its duties as a caliph on Earth according to religious guidance. In conducting this research, the authors use a library research with a qualitative approach. The results of reconstructing teaching form and fiqh assessment based on sociographic needs and the readiness of age of learners.